Asbabun Nuzul Dalam Tinjaun Syariah - Salwa Nurfauziyah Sakti; Syarifuddin Ondeng (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Asbabun Nuzul is one of the important topics in Ulumul Qur'an. As a historian who wants to explore something from the development of History must know the causes of events and their drivers, if he wants to know the essence of History. Likewise in understanding the implied content of the Qur'an. Understanding what events caused the verse to be revealed, to whom the verse was revealed, and in what context the verse was revealed. When viewed in terms of the number of causes and verses that were revealed, Asbabun Nuzul can be divided into: Ta'addud as-Sabab wa an-Nazil Wahid, and Ta'addud an-Nazil wa as-Sabab Wahid. As for when viewed from the wording of Asbabun Nuzul contained in the narration, it is divided into: Sarih or clear, and Muhtamil or containing two meanings. The benefits of knowledge about Asbabun Nuzul are very helpful in understanding the verses of the Qur'an. It is not an exaggeration what al-Wahidi said that knowing Asbabun Nuzul is an obligation and must receive primary attention. very helpful to understand verses concerning legal issues. Many people who do not know Asbabun Nuzul fall into confusion and doubt. There are even verses that cannot be understood correctly without knowing the reason.